Mechanism of dsRNA virus replication: cloning, production and structural characterization of N-terminal domain of sigmaNS - Kotounová, Eliška (Jihočeská univerzita, 2019)
Avian reovirus is an important pathogen, which causes substantial losses in poultry industry. NS protein is essential for the virus replication, however, the mechanism and assortment of genomic segments during virus replication is yet not well understood. The structure of NS is not known as previous attempts at crystallization yielded non-diffracting crystals due to the flexible regions in the molecule. This thesis deals with the production and purification of the N-terminal domain of NS, which lacks the exposed flexible region.
Mechanism of dsRNA virus replication: cloning,production and structural characterization of N-terminal domain of sigmaNS